Praksis Pendidikan Berorientasi Kebutuhan Perkembangan Anak - Dwi Priyanto (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2017)
Abstract: The demands of life in this globalization era are full of information, fast changing and full of competition, and leading people to always do creative. As a result of various changes, new demands were born in the implementation of education. The speed of the changing world's development needs to be balanced by the ability to learn fast. Classical learning, which takes little account of individual differences, and less attention to the development of children, has not been able to keep pace with the speed of world development in this globalization. To plan for education in harmony with the development of children, it means preparing students to become students who are able to learn quickly and perfectly. This means that teachers are required to understand the procedures for presenting new materials for the development of students. Experiences involving visualization (color, shape, size), auditory (sound and rhythm) and kinesthetic (sense and feeling), need to be suited to the child's developmental stage, thus strengthening and enhancing learning outcomes in accordance with this globalization demand. Keywords: educational practices, child development, individual characteristics.